Low temperature IR spectroscopy and photochemistry of matrix-isolated α-pyridil - Lopes, Susy (2008)
α-Pyridil [(C6H4NO)2] has been isolated in low temperature argon and xenon matrices and studied by FTIR spectroscopy, supported by DFT(B3LYP)/6–311++G(d,p) calculations. Calculations predicted the existence of three different conformers exhibiting skewed conformations around the intercarbonyl bond and the two C5H4NC(O) fragments nearly planar. The two higher energy forms, TCG and CCSk were estimated theoretically to be, respectively, 21.0 and 35.1 kJ mol−1 higher in energy than the most stable form, TTG. In consonance with the relatively high energies predicted by the calculations for the two less stable conformers of α-pyridil, only the most stable conformer was found spectroscopically to be present in the studied matrices. Infrared spectra obtained for the neat low temperature amorphous and crystalline states reveals that the TTG conformer is also the sole conformer present in these phases. UV irradiation (λ > 235 nm) of matrix-isolated α-pyridil led to its isomerization into unusual molecular species bearing Hückel-type pyridine (aza-benzvalene) rings.